2001
DOI: 10.1046/j.1365-2036.2001.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of triple therapy with rabeprazole for Helicobacter pylori infection and CYP2C19 genetic polymorphism

Abstract: Background: Rabeprazole is a new, potent, proton pump inhibitor. The metabolism of rabeprazole is less dependent on CYP2C19 genetic polymorphism. Methods: A total of 102 Helicobacter pylori‐positive patients with gastric ulcer were randomly allocated to three groups: rabeprazole 10 mg (RAC10), rabeprazole 20 mg (RAC20) or rabeprazole 40 mg (RAC40) plus amoxicillin 750 mg and clarithromycin 200 mg twice daily for 7 days. CYP2C19 genotype was determined by the polymerase chain reaction‐restriction fragment lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 31 publications
5
78
3
Order By: Relevance
“…Most PPIs are metabolized by cytochrome P450 in the liver. Therefore, extensive metabolizer patients do not attain sufficient PPI levels to achieve optimal pH level for antibiotic effects [89] .…”
Section: Treatment Failurementioning
confidence: 99%
“…Most PPIs are metabolized by cytochrome P450 in the liver. Therefore, extensive metabolizer patients do not attain sufficient PPI levels to achieve optimal pH level for antibiotic effects [89] .…”
Section: Treatment Failurementioning
confidence: 99%
“…The eradication rate obtained by the triple therapy consisted of proton pump inhibitor (PPI) + amoxicillin (AMPC) + clarithromycin (CAM) [PPI /AC] was about 90% in 2000 [6], but it has slightly decreased in recent years [7]. As factors in outcome of eradication therapy, age, smoking cigarettes, compliance, drug sensitivity, and genetic polymorphism of CYP2C19 have been reported, but drug resistance to CAM has been reported to be most closely involved [8][9][10][11][12][13][14][15]. However, the compliance was more than 90% in these studies because the studies were clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that there are no significant differences in the rate of eradication when any of the 3 agents, omeprazole (OPZ), lansoprazole (LPZ), and rabeprazole (RPZ), ANNALS OF Cancer Research and Therapy is used as a PPI (Miwa, Ohkura et al, 1999;Inaba, Mizuno et al,2002) however, reported that RPZ achieved a higher rate of eradication than LPZ. In addition, several studies have indicated that there are no significant differences in the rate of eradication among different doses of RPZ as a PPI, 10mg, 20mg, and 40mg (Hokari, Sugiyama et al, 2001;Miwa, Yamada et al, 2000). Similarly, there were no significant differences in the rate of eradication between 2 doses of CAM: 400mg and 800mg Hokari, Sugiyama et al, 2001;Kihira, Satoh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have indicated that there are no significant differences in the rate of eradication among different doses of RPZ as a PPI, 10mg, 20mg, and 40mg (Hokari, Sugiyama et al, 2001;Miwa, Yamada et al, 2000). Similarly, there were no significant differences in the rate of eradication between 2 doses of CAM: 400mg and 800mg Hokari, Sugiyama et al, 2001;Kihira, Satoh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation